Correlation of Sales, Business Climate Change Through Economic The Correlation of SME Sales, Business Climate Change Impact, and Economic Growth in Sustainable Green Economy Implementation - Dura, Justita; Azreen Azriana Binti Azham, Nur (Universitas Medan Area, 2024)
East Java actively promotes the concept of green economy as an integral part of its efforts to sustain national development. This concept emphasizes not only job creation, economic growth, and environmental preservation but also serves as a foundation for advancing the province further. The implementation of green economy is expected to manage natural resources sustainably while strengthening existing economic sectors. This study aims to examine the direct impacts of green economy practices on key aspects in East Java, including overall economic growth, climate change, SME sales, and their contribution to sustainable development. With a focus on over one million SMEs in the province, the study employs quantitative survey methods to gather comprehensive data. The Economic Base Theory serves as the theoretical framework, highlighting that regional economic growth is driven by external demand for local goods and services. The research aims to provide valuable insights for policymakers and economic practitioners in developing effective and sustainable green economy strategies at the regional level. It also aims to contribute positively to global efforts addressing climate change challenges and environmental conservation.